Dalits in India : Religion as a Source of Bondage or Liberation with Special Reference to Christians - Massey, James, (Brill | Manohar Publishers & Distributors, 2024)
The present work studies the subject of religion as a source of bondage or liberation with special reference to the casteless Christians. It deals with the Dalits in India in general, the history of their problems, and the basic question of their identity. The discussion of their history also includes the role of religion and how far it has acted as an agent of bondage or liberation for the Dalits. The religions which are referred to in this work are Hinduism, Buddhism, Jainism, Sikhism, Lingayatism (Veerasaivism), Christianity, Islam, Judaism, Zoroastrianism and Baha'i religion. This work discusses in detail the role of Hindu religion with special reference to the caste system. Besides Hindu religion, detailed references are made to Christian religion or faith with emphasis on casteless Christians. Christian Dalits are casteless because they belong to a community who in their pre-Dalit state were casteless and classless people. Also Christians are supposed to be casteless, because Christian religion is considered to be above caste or class.